2015
DOI: 10.18632/oncotarget.2881
|View full text |Cite
|
Sign up to set email alerts
|

Garcinol sensitizes human head and neck carcinoma to cisplatin in a xenograft mouse model despite downregulation of proliferative biomarkers

Abstract: Platinum compounds such as cisplatin and carboplatin are frequently used as the first-line chemotherapy for the treatment of the head and neck squamous cell carcinoma (HNSCC). In the present study, we investigated whether garcinol, a polyisoprenylated benzophenone can chemosensitize HNSCC to cisplatin. We found that garcinol inhibited the viability of a panel of diverse HNSCC cell lines, enhanced the apoptotic effect of cisplatin, suppressed constitutive as well as cisplatin-induced NF-κB activation, and downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 66 publications
1
50
0
Order By: Relevance
“…Twelve out of 33 compounds had a marked difference in the IC50 between Pten fl/fl and Pten À / À cells (Pten À / À IC50 r 60% Pten fl/flIC50 ) and were selected for the final step of the screening. Examples of compounds that did not pass the optimization filter despite a previous selectivity at single dosage were: Clotrimazole 8,9 , Clomipramine hydrochloride 10 , Nifedipine 11 , Trichostatin A 12,13 and Garcinol 14 (not specific cell growth arrest between Pten fl/fl and Pten À / À cells at the IC50). Finally, compounds were tested in SA-b-gal assay using both the cell lines to test for cellular senescence induction (SA-b-gal filter).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve out of 33 compounds had a marked difference in the IC50 between Pten fl/fl and Pten À / À cells (Pten À / À IC50 r 60% Pten fl/flIC50 ) and were selected for the final step of the screening. Examples of compounds that did not pass the optimization filter despite a previous selectivity at single dosage were: Clotrimazole 8,9 , Clomipramine hydrochloride 10 , Nifedipine 11 , Trichostatin A 12,13 and Garcinol 14 (not specific cell growth arrest between Pten fl/fl and Pten À / À cells at the IC50). Finally, compounds were tested in SA-b-gal assay using both the cell lines to test for cellular senescence induction (SA-b-gal filter).…”
Section: Resultsmentioning
confidence: 99%
“…Li F et al . showed that Garcinol, a natural polyisoprenylated benzophenone derivative (PPAP), chemosensitized head and neck squamous cell carcinoma b negatively regulating constitutive cisplatin-induced nuclear factor-kB activation and the expression of oncogenic gene product 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Several chemotherapeutic agents, including paclitaxel, vinblastine, vincristine, doxorubicin, and daunomycin have been reported to induce NF-κB activation in different cells However, it has also been found that the nature of the genes expressed following chemotherapy-induced NF-κB activation is context dependent and this activation can result in both the expression or suppression of anti-apoptotic genes [ 34 , 35 , 36 , 37 ].…”
Section: Nf-κb Activation By Chemotherapeutic Agentsmentioning
confidence: 99%